UNHCR'S SUPERVISORY RESPONSIBILITY - Türk, Volker (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2001)
The 1951 Convention and its 1967 Protocol created UNHCR as the international institution mandated to provide international protection to refugees, inter alia by supervising the application of this international legal regime. Supervision is defined as a legal process that empowers authorized institutions to apply certain procedures to assure the proper functioning of the legal order by inducing subjects to observe obligations incumbent on them. This paper describes UNHCR’s supervisory role within the broader context of its international mandate, analyses its content and proposes possible avenues that could be developed to enhance that role. The author points out that in the context of refugee protection, it is important to ensure the resolution of refugee problems and harmonization of international refugee law on the basis of objective evaluations and judgements.